2023
DOI: 10.1172/jci163799
|View full text |Cite
|
Sign up to set email alerts
|

IL-6 in the infarcted heart is preferentially formed by fibroblasts and modulated by purinergic signaling

Abstract: Plasma IL-6 is elevated after myocardial infarction (MI) and is associated with increased morbidity and mortality. Which cardiac cell type preferentially contributes to IL-6 and how its production is regulated is largely unknown. Here, we studied the cellular source and purinergic regulation of IL-6 formation in a murine MI model. IL-6, measured in various cell types in post MI hearts by qPCR, RNAscope and at protein level, was preferentially formed by fibroblasts (CFs). scRNAseq in infarcted mouse and human h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 64 publications
0
7
0
Order By: Relevance
“…With the deepening of research, new regulatory mechanisms of cardiac fibrosis will be revealed continuously. Consistent with previous study [ 17 ], our study reveals that fibroblasts also secrete large amounts of the inflammatory cytokine IL-6 after myocardial infarction or in response to DAMPs following myocardial infarction and confirms the important role of IL-6 produced by fibroblasts. We found that interfering with fibroblast IL-6 production significantly reduced fibroblast activation and inhibited pro-fibrotic cytokine IL-11 release mediated by STAT3.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With the deepening of research, new regulatory mechanisms of cardiac fibrosis will be revealed continuously. Consistent with previous study [ 17 ], our study reveals that fibroblasts also secrete large amounts of the inflammatory cytokine IL-6 after myocardial infarction or in response to DAMPs following myocardial infarction and confirms the important role of IL-6 produced by fibroblasts. We found that interfering with fibroblast IL-6 production significantly reduced fibroblast activation and inhibited pro-fibrotic cytokine IL-11 release mediated by STAT3.…”
Section: Discussionsupporting
confidence: 92%
“…Recently, it has also been shown that fibroblasts are also an important source of IL-6 after myocardial infarction. However, it remains unknown what role fibroblast-derived IL-6 plays in the function of fibroblasts [ 17 ]. Our study confirms that targeting fibroblast IL-6 expression also significantly improves cardiac dysfunction after myocardial infarction, providing evidence to support more precisely targeted therapy after infarction.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the JCI , Alter and colleagues elegantly implicated cardiac fibroblasts as a major source of IL-6 following coronary ligation in mice. ( 6 ) The study authors proposed a pathway that involved adenosine signaling to cardiac fibroblasts via the adenosine A2b receptor (A2bR) and provide supportive evidence from observations in human tissue.…”
Section: Cardiac Fibroblasts Produce Il-6mentioning
confidence: 61%
“…Also, 4-hour perfusion led to a 34% downregulated expression of IL-1β. Elevated levels of these markers are known to be associated with inflammatory responses, cardiac remodeling, and heart failure ( 22 , 23 ). However, their precise role in HMP and implications for clinical outcomes are yet to be delineated in future studies.…”
Section: Resultsmentioning
confidence: 99%